The Impact of Project-Based Farming Gardening on Collaboration and Critical Thinking Skills in 5-6 Year Old Children - Imara, Faridah Ummu; Fitri, Ruqoyyah; Matheos Lasarus Malaikosa, Yes; Kristanto, Andi; Dewi, Utari; Jannah, Miftakhul (Journal of Islamic Education Students (JIES), 2025)
This study aims to examine the effect of project-based farming gardening activities on collaboration and critical thinking skills of children aged 5ÔÇô6 years. The activity engages children in planning, planting, caring for, and harvesting plants for four weeks through a collaborative project that emphasizes joint decision-making, problem-solving, and individual and group responsibility. A quantitative approach with a quasi-experimental non-equivalent control group design was applied to 30 children from two kindergartens in Maduran District, Lamongan Regency, purposively divided into experimental and control groups. Data were collected through validated and reliable observation instruments, and analyzed using an independent sample t-test. The results showed a significant increase in collaboration skills (t = 3.688, p = 0.00) and critical thinking skills (t = 2.369, p = 0.02) in the experimental group. These findings indicate that project-based farming gardening activities are effective in developing collaboration and critical thinking skills in early childhood and support the strengthening of 21st-century skills in early childhood education.┬á┬á